SPINAL ANESTHESIA IN PARTURIENT WITH SEVERELY SCOLIOTIC SPINE - Sivevski, Atanas; Ivanov, Emilija; Karadjova, Dafina; Veninov, Filip; Spasovski, Sasho; Popovska, Rusanka (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2018)
The choice of anesthesia in parturients with severe scoliosis undergoing an elective cesarean section (C-section) is associated with potential risks for both mother and fetus and presents a challenge for the anesthesiologist when considering the type of anesthesia that should be used. Alterations in the maternal physiology and potential perioperative complications associated with this comorbidity can cause difficulties when both general and spinal anesthesia are used. After reviewing all risk factors associated with both types of anesthesia, we consider that a single shot spinal anesthesia can be a successful type of anesthesia in severely scoliotic individuals, especially in those with pulmonary compromise. Here we present a successful case of parturient undergoing а spinal anesthesia for C-section performed at the University Hospital for Genecology in Skopje.
Keywords: anesthesia; C-section; severe scoliosis; spinal